Synthesis, characterization and X-ray crystal structure of a new cocrystal complex of and preparation the related nano cadmium (II) oxide - Younes Hanifehpour; Babak Mirtamizdoust; Reza Golbedaghi (شیمی کاربردی روز)
In this work, A novel novel cadmium (II) co-crystal binary coordination compound with 3- FBINH ligand and nitrate anionic ligand were synthesized and characterized. The structure of co-crystal (3- FBINH is the abbreviation of 3- flouro benzylidene iso nicotine hydrazide) ([Cd (3-FBINH)2 (NO3)2 (H2O)] [Cd (3-FBINH)2 (NO3) (C2H6O) (H2O)].NO3 (1) was characterized by single-crystal X-ray analysis. The X-ray structure revealed that the compound has two Cd (II) metal centers with 7 and 6 coordination numbers. The adjacent frameworks connected by labile interactions like strong hydrogen -bonding interactions, CH …π interactions CH …CH interactions that the self-assembly occurs in the structure. Consequently, the labile interactions also allow the structure to form a 3D supramolecular coordination system. Cd O nanoparticles were obtained by thermolysis of 1 at 550 °C. The morphology and size of the prepared Cd O nanoparticles were further studied using SEM and